Linear algebra - Hoffman, Kenneth; Kunze, Ray (New Jersey: PHI Learning, 1971)
The first part of the book contains more examples concerning linear equations and computations with matrices. In addition, there are more problems of an elementary nature designed to clarify the basic computational aspects of the subject. The material on characteristic values, characteristic vectors, and diagonalization of matrices is reorganized so that the elementary and geometrically intuitive concepts are presented first.
Appendix A.1-A.6, 386-399p.; Index 401-407p.; Bibliography 400p.
Keywords: Linear algebra; Mathematics